2012
DOI: 10.1002/chem.201102660
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Proline Enamine Carboxylates by Amine Bases

Abstract: As part of our ongoing studies to provide an experimental basis for the improved understanding of organocatalytic reaction mechanisms we present a study on the influence of amine bases on enamine intermediate stabilization in proline catalysis. The (partial) deprotonation of the proline acid function is displayed by characteristic shifts of certain proton resonances and is also manifested by an increase of the amount of enamine intermediate upon reaching a critical pK(aH). Strong bases, such as 1,8-diazabicycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…Very recently, Gschwind and co-workers have explored the base-induced effect on the equilibrium among the key intermediates in proline-catalyzed reactions and the in situ NMR techniques have helped them to confirm the dominant existence of the prolinate-DBUH + ion pair (intermediate III in Scheme 2) under strong basic conditions [12]. They have proposed that the formation of the ion pair leads to the great stabilization of the active intermediate, and this ion-pair form should be the key nucleophile and responsible for the reversal of the enantioselectivity in amination.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Very recently, Gschwind and co-workers have explored the base-induced effect on the equilibrium among the key intermediates in proline-catalyzed reactions and the in situ NMR techniques have helped them to confirm the dominant existence of the prolinate-DBUH + ion pair (intermediate III in Scheme 2) under strong basic conditions [12]. They have proposed that the formation of the ion pair leads to the great stabilization of the active intermediate, and this ion-pair form should be the key nucleophile and responsible for the reversal of the enantioselectivity in amination.…”
Section: Introductionmentioning
confidence: 97%
“…For the enamine-mediated process in proline catalysis, the widely accepted Houk-List transition state model (TSA in Scheme 1), which underlines that the proton of the enamine carboxylic acid (intermediate I in Scheme 2) plays an essential role in directing the electrophile approaching the above face of s-trans-enamine in the stereocontrolling addition step, has been successfully employed to rationalize the stereoselectivity of various reactions [2,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Recently, several experimental evidences have shown that the reactivity and selectivity of the proline-catalyzed transformations are sensitive to the basic additives [7][8][9]11,12]. For instance, in 2007, Seebach and Eschenmoser demonstrated the key role of the strong basic additive (such as DBU) in the generation of the pivotal reactive intermediate (enamine carboxylate anion, intermediate II shown in Scheme 2) and explained the observed stereoselectivity in proline-catalyzed aldol and Michael reactions under basic conditions by the proposed oxazolidinone pathway (or enamine carboxylate model, TSB in Scheme 1), in which the negatively charged enamine carboxylate constitutes the nucleophilic species and the carboxylate-assisted addition of the electrophile to the below face of the s-cis-conformation of enamine intermediate II yields more stable exo-oxazolidinone product [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is supposed that DBU stabilizes the intermediately formed proline enamine. Support for this consideration is given by analysis of corresponding NMR-experiments [82]. This condensation process is followed by a stereoselective ketalization dictated by the configuration of the 2-hydroxy group of the carbohydrate (K).…”
mentioning
confidence: 99%